Knockout of NRF2 triggers prostate cancer cells death through ROS modulation and sensitizes to cisplatin. Issue 12 (3rd October 2022) - Mancini, Mariana C. S.; Morelli, Ana P.; Severino, Matheus B.; Pavan, Isadora C. B.; Zambalde, Érika P.; Góis, Mariana M.; Silva, Luiz G. S. da; Quintero‐Ruiz, Nathalia; Romeiro, Caio F.; dos Santos, Daniel F. G.; Bezerra, Rosângela M. N.; Simabuco, Fernando M.
Abstract: Prostate cancer (PCa) represents the second most common cancer in men and affects millions worldwide. Chemotherapy is a common treatment for PCa but the development of resistance is often a problem during therapy. NRF2 (nuclear factor erythroid 2‐related factor 2) is one of the major transcription factors regulating antioxidant enzymes and is also involved with drug efflux and detoxification. Cancer cells submitted to chemotherapy often promote NRF2 activation to benefit themselves with the cytoprotective response. Here, we found that DU145 and PC3 PCa cell lines have different responses regarding NRF2 activation, when subjected to arsenite‐induced stress, even in the presence of MG132, a proteasome inhibitor. We also observed that only in PC3 cells treated with arsenite, NRF2 was able to translocate to the nucleus. To better understand the role of NRF2 in promoting chemoresistance, we performed CRISPR knockout of NRF2 (NKO) in DU145 and PC3 cells. The effectiveness of the knockout was confirmed through the downregulation of NRF2 targets ( p  < 0.0001). PC3 NKO cells exhibited higher levels of reactive oxygen species (ROS) compared to wild‐type cells ( p  < 0.0001), while this alteration was not observed in DU145 NKO cells. Despite no modulation in ROS content, a lower IC50 value ( p  < 0.05) for cisplatin was observed in DU145 NKO cells, suggesting that the knockout sensitized the cells to the treatment. Besides, the treatment of DU145 NKO with cisplatin led cells to apoptosis as observed by the increased levels of PARP1 cleavage ( p  < 0.05), possibly triggered by increased DNA damage. Reduced levels of KU70 and phospho‐CHK2 ( p  < 0.05) were also detected. The data presented here support that NRF2 is a mediator of oncogenesis and could be a potential target to sensitize PCa cells to chemotherapy, reinforcing the importance of knowing the specific genetic and biochemical characteristics of the cancer cells for a more effective approach against cancer.